IDENTIFYING CRITICAL FACTORS IN LEAN IMPLEMENTATION FOR THE MANUFACTURING SECTOR: A LITERATURE REVIEW - Ubale, Satish; Aher, Dineshkumar H; Ubale, Deepali Satish (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Literature Review explores the essential aspect of lean methodologies to improve efficiency and eliminate waste while developing sustainable manufacturing practices in the manufacturing industry. The literature review focus to investigate essential lean tactics with possible implementation challenges and achievement factors to offer critical information to organizations seeking high operational efficiencies. Lean manufacturing represents a system that focuses on optimizing industrial activities by eliminating waste and developing continuous organizational improvement standards. The analysis focus on these principle because they can increase production output and fulfil sustainability targets by managing resources efficiently while minimizing environmental effects. This review demonstrates the identification of successful lean adoption enablers in addition to organizational challenges like leadership commitment obstacle and employee engagement obstacles together with change management complexities through scholarly research analysis and case study examination. Businesses can utilize the research-based practical advice to implement lean principles properly which guarantees long-term growth together with resilience and sustainability.